Establishment of a Rapid Detection Technique Based on RPA-LFD and RPA-CRISPR/Cas12a on Phytophthora pini - Tingting Dai; Yufang Guo; Tongyue Wen; Sinong Yu; Yuan Tao; Zhuo Liu (Microorganisms)
Phytophthora pini, a globally dispersed plant pathogen, poses a significant threat to natural ecosystems and cultivated horticultural crops. Early and precise detection of P. pini is essential for effective disease management. This study focused on developing specific, rapid, and sensitive molecular diagnostic techniques to identify the pathogenic oomycete P. pini. We employed recombinase polymerase amplification with lateral flow device (RPA-LFD) and RPA combined with CRISPR/Cas12a. The RPA-LFD method can identify P. pini at concentrations as low as 10 pg/μL in 30 min, while the RPA-CRISPR/Cas12a approach can detect the pathogen at 1 pg/μL in approximately 50 min. These methods are highly effective in identifying disease caused by P. pini and provide a basis for future field detection, which may reduce the economic losses associated with this devastating disease.